Upaya Peningkatan Kualitas Politisi Muda Melalui Pelatihan dan Pendidikan Politik Yayasan SATUNAMA Yogyakarta - Firdha Eka Susanti Dianingsih (Society : Jurnal Pengabdian Masyarakat, 2022)
Political education is a form of sign that we are helping to build a better state politics. Political education in politicians is a distribution to prospective leaders who will represent the community. With an unhealthy political image in Indonesia, it starts with the number of corruption figures revealed by government officials. Ignorance and generally a "return on investment" culture for politicians to recover political costs during the election period and carried out brutally while in office. Others, culture and people's knowledge in choosing leaders that are not based on actual abilities, such as choosing politicians who use money to buy votes during elections. Therefore, the Yogyakarta SATUNAMA Foundation seeks to give birth to civilized politics by providing education and education to politicians, namely the Young Politician School, so that they use a clean approach in an effort to achieve victory when running until the voting period. This education has a curriculum that designs participants until they graduate to be able to focus on development and the interests of the community so that the initial capital needed is not only with money, social capital and knowledge are the main ones. With the internship activities and outcomes regarding programs and activities during the internship, it can be used as teaching materials and information that can be absorbed by readers.